A REVIEW OF MERELY POLYMERIC NANOPARTICLES IN RECENT DRUG DELIVERY SYSTEM - PARAMESHWAR, KONDAPURAM; SAHOO, SUVENDU KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Synthetic, semi-synthetic, and natural polymers make up the colloidal formations of polymeric nanoparticles. Because of their large surface area and nanoscale size, nanoparticles have unique physical and chemical capabilities. Their distinct size, shape, and structure influence their optical characteristics, reactivity, durability, and other attributes. Supercritical fluids, in which the fluid retains a single-phase regardless of pressure, are environmentally beneficial. It is in a state of minor criticality. Because the precipitate is solvent-free, this method is environmentally friendly. Due to their qualities, they are good candidates for various commercial and marital uses, including catalysis, imaging, pharmaceutical applications, energy-based research, and ecological applications. This review provides a supercritical fluid technology-based polymeric nanoparticles overview of various forms uses, synthesis, properties, and forthcoming prospects.